2020
DOI: 10.3389/fnagi.2020.511562
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiome Signatures Are Biomarkers for Cognitive Impairment in Patients With Ischemic Stroke

Abstract: Post-stroke cognitive impairment (PSCI) is a common neuropsychiatric complication of stroke. Mounting evidence has demonstrated a connection between gut microbiota (GM) and neuropsychiatric disease. Our previous study revealed the changes in the GM in a mouse model of vascular dementia. However, the characteristic GM of PSCI remains unclear. This study aimed to characterize the GM of PSCI and explored the potential of GM as PSCI biomarkers. A total of 93 patients with ischemic stroke were enrolled in this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 86 publications
3
49
0
Order By: Relevance
“…It is found that Lachnospiraceae dynamically changed with age and positively correlated with anxiety and cognition levels (Duan et al, 2019 ; Tengeler et al, 2020 ; Liu et al, 2021 ). The abundance of Lachnospiraceae is significantly decreased in the age-matched PSCI patients (Ling et al, 2020 ). Moreover, Lachnospiraceae had a potential diagnostic value for patients with acute ischemic ST (Xiang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is found that Lachnospiraceae dynamically changed with age and positively correlated with anxiety and cognition levels (Duan et al, 2019 ; Tengeler et al, 2020 ; Liu et al, 2021 ). The abundance of Lachnospiraceae is significantly decreased in the age-matched PSCI patients (Ling et al, 2020 ). Moreover, Lachnospiraceae had a potential diagnostic value for patients with acute ischemic ST (Xiang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is speculated that the gut microbiota plays an important role in regulating the metabolic pathways of the host and plays an important role in a variety of disease phenotypes Leclercq et al, 2020;Ling et al, 2020;Shi et al, 2020b;van Soest et al, 2020). In recent years, people have realized that the microbiota-gut-brain axis is a novel concept in the field of neurological disease research (Li et al, 2020;Mao et al, 2020;FIGURE 9 | Schematic diagram showing the regulation of ZBPYR treatment on the network of differentiated bacterial and metabolite structural components.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation endpoints of WP4 include incidence of psychopathology (e.g., anxiety and depression) after stroke and related pain conditions, psychopathological issues, and coping strategies affecting adherence to rehabilitation programs, effectiveness of psychopharmacological and psychotherapeutic treatments in stroke patients, definition of specific psychological interventions supporting rehabilitation ( 17 , 18 ). Accordingly, the outcomes considered are the Symptom Checklist-90 scale ( 19 ); the Eysenck Personality Questionnaire-R ( 20 ); the COPE scale ( 21 ); the General Self-Efficacy Scale ( 22 ); the Acceptance and Action Questionnaire-II scale ( 23 ); the Multidimensional Scale of Perceived Social Support ( 24 ); the Brief Pain Inventory-I scale ( 25 ).…”
Section: Methodsmentioning
confidence: 99%
“…To identify bacterial species, present in GM, analysis of nine variable regions of 16S ribosomal RNA gene will be performed by next generation sequencing (NGS). Bioinformatical and statistical analyses will be conducted to relate gut microbiota signatures at different taxonomic levels to stroke rehabilitation conditions ( 25 ).…”
Section: Methodsmentioning
confidence: 99%